Goat casein genotypes are associated with milk production traits in the Sarda breed. (2nd July 2014) - Vacca, G. M.; Dettori, M. L.; Piras, G.; Manca, F.; Paschino, P.; Pazzola, M.
Summary The aim of the current work was to analyze, in the Sarda breed goat, genetic polymorphism within the casein genes and to assess their influence on milk traits. Genetic variants at the CSN1S1, CSN2, CSN1S2 and CSN3 gene loci were investigated using PCR‐based methods, cloning and sequencing. Strong alleles prevailed at the CSN1S1 gene locus and defective alleles also were revealed. Null alleles were evidenced at each calcium‐sensitive gene locus. At the CSN3 gene locus, we observed a prevalence of the CSN3 A and B alleles; the occurrence of rare alleles such as CSN3 B'', C, C', D, E and M; and the CSN3 S allele (GenBank KF644565) described here for the first time in Capra hircus. Statistical analysis showed that all genes, except CSN3, significantly influenced milk traits. The CSN1S1 BB and AB genotypes were associated with the highest percentages of protein (4.41 and 4.40 respectively) and fat (5.26 and 5.34 respectively) (P < 0.001). A relevant finding was that CSN2 and CSN1S2 genotypes affected milk protein content and yield. The polymorphism of the CSN2 gene affected milk protein percentage with the highest values recorded in the CSN2 AA goats (4.35, at P < 0.001). The CSN1S2 AC goats provided the highest fat (51.02 g/day) and protein (41.42 g/day) (P < 0.01) production. This information can be incorporated into selection schemes for the Sarda breed goat.